2021
DOI: 10.1096/fj.202002454rr
|View full text |Cite
|
Sign up to set email alerts
|

RNAi prodrugs decrease elevated mRNA levels of Polo‐like kinase 1 in ex vivo cultured primary cells from pediatric acute myeloid leukemia patients

Abstract: Acute myeloid leukemia (AML) is a genetically heterogeneous disease that originates from mutations in the myeloid compartment of hematopoietic cells. Of all leukemia types, AML is the most refractory to treatment and the five-year survival ranges from 40% in adults to about 70% in children. 1 Induction treatment-resistant and relapsing cases have poor prognosis. 2,3 The high incidence of treatment-related deaths indicates that the use of chemotherapy has reached its limits and other treatment options should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Several studies have demonstrated that PLK2 and PLK3 have tumor‐suppressive roles, therefore, their inhibition needs to be evaluated for some tumors and especially for normal cells. In hematological cancers, however, these PLKs are frequently silenced as we observed in T‐ALL, B‐ALL, and AML 12,24,35‐37 . In particular, the Jurkat cell lines do not express either of them, 24 confirmed by the TPP analysis (data not shown).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Several studies have demonstrated that PLK2 and PLK3 have tumor‐suppressive roles, therefore, their inhibition needs to be evaluated for some tumors and especially for normal cells. In hematological cancers, however, these PLKs are frequently silenced as we observed in T‐ALL, B‐ALL, and AML 12,24,35‐37 . In particular, the Jurkat cell lines do not express either of them, 24 confirmed by the TPP analysis (data not shown).…”
Section: Discussionsupporting
confidence: 51%
“…In hematological cancers, however, these PLKs are frequently silenced as we observed in T-ALL, B-ALL, and AML. 12,24,[35][36][37] In particular, the Jurkat cell lines do not express either of them, 24 confirmed by the TPP analysis (data not shown). Therefore, we could not assess how their T agg changes upon volasertib and onvansertib treatment.…”
Section: Discussionmentioning
confidence: 55%
“…PLK1 is overexpressed in various hematological malignancies, according to previous studies 17,24,25 . A study claims that PLK1 in peripheral blood and BMMCs is higher in pediatric AML patients than in healthy controls 24 .…”
Section: Discussionmentioning
confidence: 92%
“…17,24,25 A study claims that PLK1 in peripheral blood and BMMCs is higher in pediatric AML patients than in healthy controls. 24 PLK1 in peripheral blood leukocytes is also increased in chronic myeloid leukemia patients compared with healthy controls. 25 In pediatric ALL patients, the dysregulation of PLK1 is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation